Histone methyltransferase DOT1L controls state‐specific identity during B cell differentiation. (7th January 2021) - Aslam, Muhammad Assad; Alemdehy, Mir Farshid; Kwesi‐Maliepaard, Eliza Mari; Muhaimin, Fitriari Izzatunnisa; Caganova, Marieta; Pardieck, Iris N; van den Brand, Teun; van Welsem, Tibor; de Rink, Iris; Song, Ji‐Ying; de Wit, Elzo; Arens, Ramon; et al.
Abstract: Differentiation of naïve peripheral B cells into terminally differentiated plasma cells is characterized by epigenetic alterations, yet the epigenetic mechanisms that control B‐cell fate remain unclear. Here, we identified a role for the histone H3K79 methyltransferase DOT1L in controlling B‐cell differentiation. Mouse B cells lacking Dot1L failed to establish germinal centers (GC) and normal humoral immune responses in vivo . In vitro, activated B cells in which Dot1L was deleted showed aberrant differentiation and prematurely acquired plasma cell characteristics. Similar results were obtained when DOT1L was chemically inhibited in mature B cells in vitro . Mechanistically, combined epigenomics and transcriptomics analysis revealed that DOT1L promotes expression of a pro‐proliferative, pro‐GC program. In addition, DOT1L indirectly supports the repression of an anti‐proliferative plasma cell differentiation program by maintaining the repression of Polycomb Repressor Complex 2 (PRC2) targets. Our findings show that DOT1L is a key modulator of the core transcriptional and epigenetic landscape in B cells, establishing an epigenetic barrier that warrants B‐cell naivety and GC B‐cell differentiation. SYNOPSIS: The histone H3K79 methyltransferase DOT1L plays a central role in B cell development and differentiation. DOT1L maintains B cells naivety by orchestrating critical transcriptional and epigenetic regulators. DOT1L is essential for the formation of germinal center B cells. DOT1L prevents premature differentiation of naïve B cells towards plasma cells. DOT1L contributes to the repression of PRC2 target genes. Abstract : The histone H3K79 methyltransferase DOT1L plays a central role in B cell development and differentiation. DOT1L maintains B cells naivety by orchestrating critical transcriptional and epigenetic regulators.